Aplikasi Mudah Istilah Teknikal (AMIT): empowering the Bahasa Malaysia technical terminology using electronic application/ Kamisah Ariffin ... [et al.] - Ariffin, Kamisah; Mohd Nor, Nur Asmaliza; Alias, Asmidar; Abu Hashim, Anis Hasliza (2015)
Most technical students in this country, especially in the engineering field, have little exposure to technical terminology in Bahasa Malaysia (BM). This is because the term references are mostly available in English. The only bilingual reference published by Dewan Bahasa dan Pustaka (DBP) is in the hard copy version, which is bulky, therefore, inconvenient, and outdated. Students, thus, often face difficulties in expressing themselves, both in writing and speaking, in BM as technical terms in BM seem to be alienated during their academic terms. Likewise, engineering practitioners and those involved in the field (in Malaysia) often find it difficult to explain the terminology when they need to communicate with the locals. With the ardent availability of technological application these days, one of the fastest ways to retrieve information is through apps software. However, to date, available electronic dictionary apps for engineering terms are all in English. Thus, the need of Bahasa Malaysia apps is anticipatable. An electronic bilingual dictionary named, Aplikasi Mudah lstilah Teknikal (AMIT), is proposed as a solution to the situation. This paper focuses on the development of AMIT. Supported by mobile application development life cycle method (MADLC), software, such as PHP and Eclipse, together with Java programming language, was used in developing the application. Other important requirements such as target audience, user interface, accessibility and the use of search keyword were implemented in this application.